Nanosuspension-Loaded Dissolving Microneedle Patches for Enhanced Transdermal Delivery of a Highly Lipophilic Cannabidiol - Cheng A; Zhang S; Meng F; Xing M; Liu H; Yang G; Gao Y (International Journal of Nanomedicine, 2024)
Aguo Cheng,1,2 Suohui Zhang,1,3 Fanda Meng,4 Mengzhen Xing,5 Han Liu,3 Guozhong Yang,3 Yunhua Gao1– 3 1Key Laboratory of Photochemical Conversion and Optoelectronic Materials, Technical Institute of Physics and Chemistry of Chinese Academy of Sciences, Beijing, People’s Republic of China; 2University of Chinese Academy of Sciences, Beijing, People’s Republic of China; 3Beijing CAS Microneedle Technology Ltd, Beijing, People’s Republic of China; 4School of Clinical and Basic Medical Sciences, Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong Province, People’s Republic of China; 5Key Laboratory of New Material Research Institute, Department of Pharmaceutical Research Institute, Shandong University of Traditional Chinese Medicine, Jinan, Shandong Province, People’s Republic of ChinaCorrespondence: Yunhua Gao, Key Laboratory of Photochemical Conversion and Optoelectronic Materials, Technical Institute of Physics and Chemistry of Chinese Academy of Sciences, Beijing, People’s Republic of China, Tel +86 (10)82543581, Email yhgao@mail.ipc.ac.cnPurpose: Transdermal Drug Delivery System (TDDS) offers a promising alternative for delivering poorly soluble drugs, challenged by the stratum corneum’s barrier effect, which restricts the pool of drug candidates suitable for TDDS. This study aims to establish a delivery platform specifically for highly lipophilic drugs requiring high doses (log P > 5, dose > 10 mg/kg/d), to improve their intradermal delivery and enhance solubility.Methods: Cannabidiol (CBD, log P = 5.91) served as the model drug. A CBD nanosuspension (CBD-NS) was prepared using a bottom-up method. The particle size, polydispersity index (PDI), zeta potential, and concentration of the CBD-NS were characterized. Subsequently, CBD-NS was incorporated into dissolving microneedles (DMNs) through a one-step manufacturing process. The intradermal dissolution abilities, physicochemical properties, mechanical strength, insertion depth, and release behavior of the DMNs were evaluated. Sprague-Dawley (SD) rats were utilized to assess the efficacy of the DMN patch in treating knee synovitis and to analyze its skin permeation kinetics and pharmacokinetic performance.Results: The CBD-NS, stabilized with Tween 80, exhibited a particle size of 166.83 ± 3.33 nm, a PDI of 0.21 ± 0.07, and a concentration of 46.11 ± 0.52 mg/mL. The DMN loaded with CBD-NS demonstrated favorable intradermal dissolution and mechanical properties. It effectively increased the delivery of CBD into the skin, extended the action’s duration in vivo, and enhanced bioavailability. CBD-NS DMN exhibited superior therapeutic efficacy and safety in a rat model of knee synovitis, significantly inhibiting TNF-α and IL-1β compared with the methotrexate subcutaneous injection method.Conclusion: NS technology effectively enhances the solubility of the poorly soluble drug CBD, while DMN facilitates penetration, extends the duration of action in vivo, and improves bioavailability. Furthermore, CBD has shown promising therapeutic outcomes in treating knee synovitis. This innovative drug delivery system is expected to offer a more efficient solution for the administration of highly lipophilic drugs akin to CBD, thereby facilitating high-dose administration. Keywords: nanosuspension, highly lipophilic drugs, dissolving microneedle, cannabidiol, knee synovitis